Evaluation And Analysis Of Decision-Making on the Business Method of hhe Paseh's Strategic Business Unit (SBU) For The Stones And Non-Metallic Mine At Jasa Sarana (Bumd Of West Java) - Topan Ardiansyah Putra; Pri Hermawan (Journal of Economics and Business UBS, 2023)
Jasa Sarana is a BUMD Holding of the West Java Provincial Government engaged in Infrastructure. In running its business, Jasa Sarana applies the Business Strategic Unit (SBU), a rock and non-metal mineral mining business. It was initiated in 2005-2006, with a mining area of 19.45 hectares, with rock mineral resource reserves of 3.3 million BCM. However, it could only do optimized by 24% over 16 years. If done correctly, the mining business plan must be implemented for only 15 years. With a target Payback Period of 3.35 Years, an NPV of Rp. 1,641,000,000, and IRR of 20.44%. The remaining rock mineral resources currently available are 2.5 million BCM, expected to be re-developed and generate profits for the company. Jasa Sarana has carried out preparatory steps, including conducting feasibility studies and exploratory research on this mining business unit. It did expect that the losses suffered by the company could recover in a fast time. Decision-making on the right ways and methods to reactivate this Business Unit becomes a concentration of research, consisting of situation assessment, decision analysis, and analysis of potential problems. An evaluation of the situation determines the conditions and causes of business operations underperforming externally and internally. Several problems were revealed, such as corruption, mis-partners, ineffective work methods, to improper handling of mining techniques, which became the root of the problem. Jasa Sarana has several options for handling this Business Unit with several alternatives. Including running this business unit owned by providing additional capital and recruiting competent experts, looking for the right partner with the qualifications of an experienced partner, or even selling this business unit so that it does not become a burden on the company.